Study on international carbon emission quota allocation of shipping industry-based on fairness and efficiency - Hu, Zijiang; Huang, Yiye; Sun, Ling; Qi, Xinzhou; Pan, Xianghui (Frontiers in Marine Science, 2023)
In 2024, the EU intends to include the global shipping industry in the European Union Emission Trading Scheme (EU ETS). Shipping companies will have to pay for the carbon emissions of ships over 5,000 GT on routes between EU and non-EU ports. This paper selects typical shipping companies in the world. Based on the principle of fairness, historical method, baseline method and mixed method are adopted to explore their carbon emission quota allocation. The ZSG-DEA efficiency model is used to evaluate the distribution results and verify the optimal efficiency. The research results show that the mixed method has a high efficiency of allocation. The method predicts that the carbon quota of typical shipping companies in the world will reach the Pareto optimal allocation in 2024 and Maersk has the highest carbon emission quota among the eight typical shipping companies, reaching 32,431,800 tons, followed by MSC and EMC, reaching 8,542,400 tons and 6,809,500 tons, respectively. Based on the results, we can obtain a reasonable allocation of carbon allowances in the EU carbon market according to the proportion of business of shipping companies involved in EU routes. The research is still applicable to the allocation of carbon emmissions in future years. Therefore, this paper provides suggestions for the orderly allocation of carbon quota and carbon trading in the global shipping market.